The Łódź Congress and the Revival of the Polish Scouting and Guiding Association in 1956 - Głowacka-Sobiech, Edyta (Biuletyn Historii Wychowania, 2018)
The “post-October” revival, so visible in the Polish society at the end of 1956, was clearly marked by the scouting group. The group had already shown some impatience and radicalism, as issues related to scouting had been waiting for solutions on the part of the authorities for a long time. The congress in Łódź reactivated scouting. At the same time, it showed that everything that was happening inside the organization was nothing but a reflection of the processes taking place in society. The so-called October revolution did not have much in common with a real revolution, the October transformation would be a better term, as only a slight correction of the political system took place. ZHP was still limited by the system and greatly influenced by politics. That is why the “freedom”, regained in Łódź, turned out to be an illusion.